Left-handedness without absorption in the four-level Y-type atomic medium - 赵顺才 刘正东 吴奇宣 (Chinese physics B, 2010)
In this paper we have investigated three external fields interacting with the four-level Y-type atomic system described by the density-matrix approach. The results show that left-handedness with zero absorption is achieved. The zero absorption property displays the possibility of manipulation by varying the phase and the intensity of the coupling field. Also, the zero absorption property may be used to amplify the evanescent waves that have been lost in imaging by traditional lenses. We propose an approach to obtain a negative refractive medium with zero absorption and the possibility of enhaneeingthe imaging resolution in realizing ＇superlenses＇.